1996
DOI: 10.1128/cdli.3.5.590-593.1996
|View full text |Cite
|
Sign up to set email alerts
|

Unusually high seroprevalence of Borna disease virus in clade E human immunodeficiency virus type 1-infected patients with sexually transmitted diseases in Thailand

Abstract: The seroprevalence of Borna disease virus (BDV) in human immunodeficiency virus type 1-infected individuals in Thailand was examined by using recombinant BDV p24. A high (38 to 48%) rate of seroprevalence of BDV was observed in clade E-infected patients with sexually transmitted diseases, compared with those in clade E-infected prostitutes (8.3%), pregnant women (0%), clade B-infected intravenous-drug users (0%), and human immunodeficiency virus type 1-negative blood donors (1.9%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…users and pregnant women analyzed in the same study (165). HIV-1 clade E-infected patients with STD appear to rapidly progress to AIDS (166,167), suggesting that clade E may be more virulent than clade B.…”
Section: Immunosuppressive Disordersmentioning
confidence: 92%
See 1 more Smart Citation
“…users and pregnant women analyzed in the same study (165). HIV-1 clade E-infected patients with STD appear to rapidly progress to AIDS (166,167), suggesting that clade E may be more virulent than clade B.…”
Section: Immunosuppressive Disordersmentioning
confidence: 92%
“…In addition, BDV seroprevalence was found to be very high (about 40%) in HIV-1 clade E-infected patients with sexually transmitted diseases (STD) in Thailand, compared to the prevalence found in clade E-infected prostitutes (8.3%), and HIV-1negative blood donors (1.9%) (165). BDV seropositives were not found among clade B-infected intravenous drug Sections from hippocampus and cerebellum from P1 and P2 cases, which were negative and positive for BDV 'P' RNA by RT-PCR, respectively, were subjected to ISH using a BDV 'P' antisense riboprobe.…”
Section: Immunosuppressive Disordersmentioning
confidence: 99%
“…Detection of anti-BDV antibodies. Anti-BDV antibodies in serum and plasma samples were detected by enzyme-linked immunosorbent assay (ELISA) or immunoblotting with peroxidase-conjugated rabbit immunoglobulin G (IgG) fraction to sheep immunoglobulin G (Organon Teknika Corporation, Durham, N.C.), as previously described (2,22). The BDV antigens for these assays are ORF I and ORF II, coding for p40 nucleoprotein and p24 polymerase cofactor, respectively (12,35).…”
Section: Methodsmentioning
confidence: 99%
“…We could demonstrate very low-level BDV antibody positivity among patients with HIV infection and chronic fatigue syndrome, although there are some reports of high seroprevalence among patients with these diseases. Auwanit et al (2) reported an unusually high seroprevalence of BDV in HIVinfected patients by ELISA with GST-BDV p24 (full-length) fusion protein as the antigen, and Nakaya et al (15) also reported that six of 25 chronic fatigue syndrome patients were positive for BDV by WB with the same GST-BDV p24 fusion protein. In our ECLIA system, some sera from HIV-infected patients have had high counts over the cutoff level at first screening, but all except one were judged negative by a specific inhibition test.…”
Section: Discussionmentioning
confidence: 99%